Analisis Supply Chain Management Udang di Muaro Sunur Kecamatan Nan Sabaris Kabupaten Padang Pariaman (Studi Kasus pada Nezi Farm) - Armel Yentifa; Aulia Nurrahmawati; Nurul Fauzi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine, analyze and evaluate the shrimp supply chain management a the Nezi Farm Shrimp Farm in Muaro Sunur, Nan Sabaris District, Padang Pariaman Regency using the SCOR model. This research uses a qualitative approach with a case study method. Data was collected from an in-depth interview process with the Nezi Farm shrimp farm and documentation. The results of this research indicate that the Shrimp Supply Chain Management at the Nezi Farm Shrimp Farm has been carried out well based on the results of interviews with the SCOR level 1-4 model. However, there is a performance evaluation on this shrimp pond so that it can improve performance in the future by adopting automation technology and using autofeeders so that cultivation activities can be maximized in the future and can produce high quality shrimp in every cultivation process and minimize harvest failures